The Effect of the 7e’s Course on Learning Some Basic Skills Football for Students - Jassim Hussain, Dhafer; Nugashm Yousef, Saud (International Journal of Psychosocial Rehabilitation, 2020)
Among what the Ministry of Education emphasized in the physical education teacher’s guide for the intermediate stage is the use of modern and various strategies that simulate the students ’need for education in order to arouse their motivations, inclinations and desires, and from here the researcher used the strategy of the seven-course learning (7E’s), which is one of the constructive work strategies that have been applied in the theoretical Here the teacher’s creativity in learning motor skills and their application on the practical side is shown in various games, including the game of football, which is one of the lessons that fall within the curriculum of the physical education teacher for the middle stage, which is characterized by the multiplicity of basic skills, including rolling, handling, and suppression, and then the researcher asked, Does the 7E’s course help students build? The study aimed to identify the differences between the pre- and post tests for the experimental and control groups, and to identify the post-tests for the experimental and control groups in learning some basic skills of football for students, and the researchers used the experimental approach as students were selected (second grade) intentionally division (A) and (B) The research sample consisted of (40) students; the sample was divided into two groups, an experimental group (division A) and a control group division (B), with (20) students for each group. The experimental group used the educational method in the method of the seven-course learning strategy (7E’s) The educational curriculum was in the style followed by the teacher, and the researcher used the statistical bag (SPSS), and the researcher concluded that learning the basic skills in football with the seven-circuit learning strategy (7E’s) has a greater impact than the method used by the teacher, and among what the researchers recommended was conducting more research and studies on learning with the strategy of the Seven E course (7’s) and other methods in teaching game skills such as basketball, volleyball, handball, and the rest of the games.